2001
DOI: 10.1086/501830
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Diabetes and Glucose Control With Surgical-Site Infections Among Cardiothoracic Surgery Patients

Abstract: Postoperative hyperglycemia and previously undiagnosed diabetes are associated with development of SSIs among cardiothoracic surgery patients. Screening for diabetes and hyperglycemia among patients having cardiothoracic surgery may be warranted to prevent postoperative and chronic complications of this metabolic abnormality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
293
2
17

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 497 publications
(320 citation statements)
references
References 36 publications
8
293
2
17
Order By: Relevance
“…In DM patients who underwent major non‐cardiac surgery, a hemoglobin (Hb) A1c level of <7% was significantly associated with decreased infectious complications with an adjusted odds ratio (OR) of 2.13 9. In contrast, Latham et al 8.…”
Section: Introductionmentioning
confidence: 99%
“…In DM patients who underwent major non‐cardiac surgery, a hemoglobin (Hb) A1c level of <7% was significantly associated with decreased infectious complications with an adjusted odds ratio (OR) of 2.13 9. In contrast, Latham et al 8.…”
Section: Introductionmentioning
confidence: 99%
“…However, this risk is doubled in patients with post-operative hyperglycemia, defined as BG (blood glucose) > 200 mg/dL following surgery through POD (post-operative day) 2 [2]. In 2003, the CMS (Centers for Medicare and Medicaid Services) and the CDC (Centers for Disease Control and Prevention) established the SCIP (Surgical Care Improvement Project) to help reduce post-surgical complications.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] Hyperglycemia is also a risk factor for surgical infection in patients undergoing cardiac surgery. 9,10 A landmark prospective randomized controlled clinical trial by van den Berghe et al 11 demonstrated that tight glucose control (target blood glucose level 80-110 mg/dL) with intravenous insulin in critically ill surgical patients led to dramatic reductions in acute renal failure, critical illness polyneuropathy, hospital mortality, and bloodstream infection. Other clinical studies have demonstrated that glycemic control with intravenous insulin improves clinical outcomes and reduces length of stay in patients with diabetes undergoing cardiac surgery.…”
mentioning
confidence: 99%